1993
DOI: 10.1111/j.1432-1033.1993.tb17576.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the γ‐subunit gene of desulfoviridin‐type dissimilatory sulfite reductase and of the α‐ and β‐subunit genes is not coordinately regulated

Abstract: 51 that desulfoviridin, the dissimilatory sulfite reductase of sulfate-reducing bacteria of the genus Desulfovibrio, contains a third, y, subunit (1 1 kDa), in addition to the well-established a (50 kDa) and p (40 kDa) subunits, and an a 2 j z y z subunit structure has been proposed. Cloning and sequencing of the dsvC gene indicated it to encode a protein of 105 amino acids (1 1.9 kDa; y subunit). The finding that the dsvC gene, located on a 3.5-kb SacII fragment, is transcribed in both Escherichia coli and De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 25 publications
(20 reference statements)
1
30
0
Order By: Relevance
“…The sulfite reductase-encoding genes dsrAB can be linked with dsrN and in one case also with dsrC (42,44). dsrC constitutes an independent transcriptional unit in D. vulgaris (36) and is also located apart from dsrAB in the hyperthermophilic archaeal sulfate reducer Ag. fulgidus (40).…”
Section: Discussionmentioning
confidence: 99%
“…The sulfite reductase-encoding genes dsrAB can be linked with dsrN and in one case also with dsrC (42,44). dsrC constitutes an independent transcriptional unit in D. vulgaris (36) and is also located apart from dsrAB in the hyperthermophilic archaeal sulfate reducer Ag. fulgidus (40).…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting aspect of Dvir is that it forms a stable complex with a smaller protein of 11 kDa, initially classified as a third subunit of dSiR (Pierik et al, 1992), but later identified as the DsrC protein. DsrC is encoded separately from DsrAB, the two subunits of dSiR and their expression is not coordinately regulated (Karkhoff-Schweizer et al, 1993). It is actually one of the most highly expressed proteins in Desulfovibrio vulgaris Hildenborough, with twice the expression level of DsrAB (Haveman et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Initial reports described DsrC as a ␥ subunit of dSiRs present in a stoichiometry of ␣ 2 ␤ 2 ␥ 2 (23). However, the dsrC gene is located separately from dsrAB in several sulfate-reducing organisms, like Desulfovibrio vulgaris Hildenborough, where its expression is not coordinately regulated (24). There are also several dSiRs that do not include DsrC (5, 7), but all organisms that contain the dsrAB genes include also dsrC.…”
mentioning
confidence: 99%